2012
DOI: 10.1016/j.scient.2011.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal complexation on acidity of cytosine nucleosides: Part I, Li+, Na+ and K+ cation

Abstract: Gas-phase acidities of nucleosides, combined with the knowledge of deprotonation sites, could improve our understanding of chemical reactions to biological systems. In this paper, we mainly focus our attention on the influence of cation coordination on acidities of multiple sites in cytosine nucleosides. The acidities of multiple sites in M + -L (where L represents cytosine nucleosides and M + is an alkali metal ion, including Li + , Na + and K + ) complexes have been investigated theoretically, employing B3LY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…A few examples come from computational works: a DFT study of formamide self-exchange reaction showed that PCET was changed to hydrogen-atom transfer (HAT) by metal ion coordination, which shifted the ET site from the oxygen pair to the nitrogen pair . Similarly, the metal ion was shown to influence radical type and ET channels in imide PCET reactions, and nucleoside acidity was found to be heightened by metal ion complexation . As for experimental works, flavin E -pH diagrams in aqueous environment were found to be transformed by the addition of metal ions, and more recently the influence of metal ions, protonation, and hydrogen bonding on flavin was investigated in aprotic solutions .…”
Section: Introductionmentioning
confidence: 99%
“…A few examples come from computational works: a DFT study of formamide self-exchange reaction showed that PCET was changed to hydrogen-atom transfer (HAT) by metal ion coordination, which shifted the ET site from the oxygen pair to the nitrogen pair . Similarly, the metal ion was shown to influence radical type and ET channels in imide PCET reactions, and nucleoside acidity was found to be heightened by metal ion complexation . As for experimental works, flavin E -pH diagrams in aqueous environment were found to be transformed by the addition of metal ions, and more recently the influence of metal ions, protonation, and hydrogen bonding on flavin was investigated in aprotic solutions .…”
Section: Introductionmentioning
confidence: 99%